Differentiation of Andean and Mesoamerican accessions in a proposed core collection of grain amaranths - Blair, Matthew W.; Londoño, Jorge M.; Buitrago-Bitar, María A.; Wu, Xingbo; Brenner, David M. (Frontiers in Plant Science, 2023)
Grain amaranths are made up of three New World species of pseudo-cereals with C4 photosynthesis from the dicotyledonous family Amaranthaceae and the genus Amaranthus. They originate in two ecoregions of the Americas, namely, the inter-Andean valleys of South America and the volcanic axis and lowlands of Mexico and Central America. These correspond to two centers of domestications for Andean and Mesoamerican crops, with one cultivated species found in the first region and two found in the latter region. To date, no core collection has been made for the grain amaranths in the United States Department of Agriculture (USDA) germplasm system. In this study, our objective was to create a core for the 2,899 gene bank accessions with collection site data by town or farm site of which 1,090 have current geo-referencing of latitude and longitude coordinates. We constituted the core with 260 genotypes of Amaranthus, which we evaluated with 90 single-nucleotide polymorphism markers. Our goal was to distinguish between Andean and Mesoamerican gene pools of amaranths, including the cultivated species and three possible progenitor or wild relative ancestors along with two more species in an outgroup. Population structure, clustering, and discriminant analysis for principal components showed that Andean species Amaranthus caudatus and Amaranthus quitensis shared fewer alleles with Mesoamerican species Amaranthus cruentus and Amaranthus hypochondriacus, compared to each group individually. Amaranthus hybridus was a bridge species that shared alleles with both regions. Molecular markers have the advantage over morphological traits at quickly distinguishing the Andean and Mesoamerican cultivars and have the added benefit of being useful for following inter-species crosses and introgression.